Planning of Number and Location of New Base Transceiver Station (BTS) Tower in Mobile Telecommunication System in Jombang Using Analytical Hierarchy Process Method and Geographic Information System Approach - Achmad Mauludiyanto; Yoga Dwi Pranata (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
Technology and telecommunication industry has been growing rapidly. Operators continue to race to be able to improve its services. One of them is the development of BTS to be able to serve mobile users in the area to be reached. But development without proper planning can have a bad impact in the future. This research discussed about the location arrangement and number of BTS in Jombang regency up to 5 years according to Analytical Hierarchy Process method with population density criteria, RTRW and distance and will be displayed in digital map based on geographic information system. For 2014 there are 204 towers in Jombang while for 2019 it takes 231 towers to cover the needs of the people of Jombang Regency.Keywords: analytical hierarchy process, BTS, coverage, geographic information system, traffic capacity.